Black Theology and the Black Panthers - Bartholomew, Joshua S. (Lexington Books, 2023)
In Black Theology and The Black Panthers, Joshua S. Bartholomew deals with the relationship between economic justice and racial equality. By examining the economic philosophies and inter-communal survival programs of the Black Panther Party for Self-Defense from 1967-1971, Bartholomew utilizes a Womanist methodology to connect the praxis of The Panthers with priorities of Black Theological Ethics. In doing so, Bartholomew offers a basis for moving Christian ethicists away from normative models of economic justice that eschew experience and knowledge from marginalized communities. Ultimately, Bartholomew reveals how the power of racial politics for radical change can constructively and inclusively impact the struggle for freedom and social justice.